2019
DOI: 10.1111/jan.13936
|View full text |Cite
|
Sign up to set email alerts
|

The modulating role of gender and aggression in emotional reactions of nursing students: A cross‐sectional study

Abstract: Aims To examine whether and to what extent emotion reactions of nursing students are affected by emotional features inherent in nursing care situations, focusing on gender and aggression. Background How individual characteristics of nurse students interact with emotional demands inherent in nursing practice and modulate the way they are perceived and acted upon may have an impact on quality of patient care. Design Cross‐sectional study, conducted from May to September 2013. Methods Nursing students (N = 157) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Such pressures are not borne equally by male and female students though, as indicated by the significant gender differences revealing females to be more prone to poor wellbeing outcomes compared to male students. Females also scored higher than males in trait anxiety and lower in mindfulness facets of Nonjudging and Nonreacting to experiences, suggesting a higher anxiety susceptibility in this subgroup, which is in line with independent studies on lay persons and nursing student samples (Dyrbye et al, 2006;Fino et al, 2018;Soysa & Wilcomb, 2015;Zeng et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Such pressures are not borne equally by male and female students though, as indicated by the significant gender differences revealing females to be more prone to poor wellbeing outcomes compared to male students. Females also scored higher than males in trait anxiety and lower in mindfulness facets of Nonjudging and Nonreacting to experiences, suggesting a higher anxiety susceptibility in this subgroup, which is in line with independent studies on lay persons and nursing student samples (Dyrbye et al, 2006;Fino et al, 2018;Soysa & Wilcomb, 2015;Zeng et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…They are also consistent with Colonnello et al (2019), who found that medical students can modulate avoidance/approach responses to emotion expressions of untrustworthy people by means of an aware activation of their own relational resources in the healthcare professional context. Finally, results from correlations with personality traits allow us to identify individual characteristics of caretaking professionals that could facilitate or pose barriers to the provision of impartial care, consistent with the personality modulation of emotional reactions of nursing students we previously found in an earlier study (Fino, Di Campli, Patrignani, & Mazzetti, 2019). This is especially important for untrustworthy‐looking patients who would trigger, most likely involuntarily, untrusting and avoidant behaviors in the caretaker.…”
Section: Discussionsupporting
confidence: 83%
“…Among healthcare professions, nursing is perhaps the most demanding as it requires delivering compassionate care in often stressful and adverse conditions and to effectively navigate complex interpersonal relations with patients, families and other healthcare professionals [10,11]. If more insecurely attached individuals cope less well with stress, are tendentially ill-equipped in mentalization capacities that facilitate interpersonal relationships and are more prone to burnout, then adult attachment insecurities and poor mentalization capacity may be expected to predict burnout in nurse professionals.…”
Section: Introductionmentioning
confidence: 99%